Psychological and digital factors of student attitudes towards multitasking - E. I. Rasskazova; G. U. Soldatova (Russian State Vocational Pedagogical University, 2023)
Introduction. Despite the evidence from the cognitive approach that performance decreases under multitasking conditions, multitasking is increasingly seen as an important skill to develop, especially among young people.Aim. The present research aims to reveal personal (personal traits, satisfaction of basic needs) and digital (user activity, combined activity, attitude to technology, digital competence) factors of subjective assessment of multitasking in students and their attitude to multitasking.Methodology and research methods. In the course of the research, 260 students of Moscow universities answered questions about their multitasking and their attitude to it, and then filled out the scales for assessing subjective well-being, attitudes towards learning, personal traits, basic psychological needs, user and combined activity, attitudes to technology, digital competence and the desire for digitalisation of education. The data were processed using descriptive statistics, Pearson's correlation analysis, group comparison methods (Pearson's Chi-square, Student's t-test).Results. According to the estimates of the students, they spend almost half of their daytime combining different activities. Most of students consider multitasking as a useful skill and would like to improve it. Higher multitasking scores are associated with greater conscientiousness, openness to experience, competence, positive emotions, as well as technophilia, digital skills. The desire to improve own multitasking is higher among students with a higher level of combined activity, technophilia, technorationality, as well as among students, who higher estimate the opportunities of digitalisation in education. Two out of three students consider multitasking as a useful ability; every second student thinks that multitasking can be developed by training. Multitasking and the desire to improve it are related to the attitude towards multitasking as a trained and developed skill, while the idea of its usefulness or uniqueness is practically not related to psychological and digital factors. Further research may be aimed at revealing relationships between subjective multitasking with activity diary data and experimentally organised multitasking.Scientific novelty. The attitude to multitasking format among young people was investigated from the perspective of a comprehensive approach, which combines personal characteristics and peculiarities of online activity.Practical significance. The peculiarities of students' attitudes towards multitasking as a personal choice of doing several things simultaneously, reflecting among other things a positive attitude towards multitasking and a desire to develop it, can become a significant component to develop educational programmes, as well as important knowledge to provide interaction between teachers and students under the conditions of digitalisation in education.